2020
DOI: 10.14202/vetworld.2020.1771-1779
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of antimicrobial resistance and enterobacterial repetitive intergenic consensus-PCR as a molecular typing tool for Salmonella spp. isolated from poultry and humans

Abstract: Background and Aim: Salmonella spp. are one of the most important food-borne pathogens in the world, emerging as a major public health concern. Moreover, multidrug-resistant (MDR) strains have been isolated from salmonellosis outbreaks, which compromise its treatment success. This study was conducted to characterize the phenotypic and genotypic antibiotic resistance profile of Salmonella strains isolated from broilers and humans from the regions of Tolima and Santander (Colombia). Materials and Methods: Salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
1
7
1
Order By: Relevance
“…This supports the notion that multidrug resistance from poultry-sourced Salmonella is capable of transferring human-infecting Salmonella, affecting the treatment of Salmonella infections in humans [17,18]. Reports of increasing AMR in Salmonella are appearing in both agriculture and humans, with high resistance, especially to amoxicillin (20% to 100%) and streptomycin (16.8% to 67.5%), which in addition to treating Salmonella infections is also used to treat a variety of other illnesses in humans [8,[17][18][19][20][21].…”
Section: Antimicrobial Resistance In Agriculturesupporting
confidence: 63%
“…This supports the notion that multidrug resistance from poultry-sourced Salmonella is capable of transferring human-infecting Salmonella, affecting the treatment of Salmonella infections in humans [17,18]. Reports of increasing AMR in Salmonella are appearing in both agriculture and humans, with high resistance, especially to amoxicillin (20% to 100%) and streptomycin (16.8% to 67.5%), which in addition to treating Salmonella infections is also used to treat a variety of other illnesses in humans [8,[17][18][19][20][21].…”
Section: Antimicrobial Resistance In Agriculturesupporting
confidence: 63%
“…In Columbia, Herrera-Sanchez et al [ 76 ] reported similar ERIC banding patterns consisting of 2—13 bands that ranged from 200 to 4000 bp in size whilst contrasting ERIC results of band sizes 15—1500 bp and 190—1430 bp were observed by Fendri et al [ 77 ] in France and Oliveria et al [ 78 ] in Brazil, respectively. Among the 210 isolates, there were various patterns and clusters.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have reported that S . Paratyphi B isolated from poultry products in Colombia [ 14 , 43 ] have remarkable antibiotic resistance, and 22/24 Salmonella Paratyphi B isolates in this study were resistant to three antibiotic classes, penicillins (ampicillin), aminoglycosides (streptomycin), and cephalosporins (ceftriaxone and ceftazidime), that may have an impact in the treatments of human infections [ 44 ]. Furthermore, antimicrobial resistance constitutes a global trend and international food trading restrictions could be pressuring drivers to promote control of Salmonella in Colombia [ 33 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%